PREVALENCE OF OBESITY AND ITS IMPLICATIONS FOR DIABETES AND HYPERTENSION RISK - Ismail Ismail (Persatuan Perawat Nasional Indonesia (JPPNI), 2025)
Objective: This study aimed to determine the prevalence of obesity and assess its implications for the risk of diabetes and hypertension based on anthropometric and metabolic parameters. Methods: A cross-sectional study was conducted among employees of the Nursing Department at Makassar Polytechnic in 2025. A total of 42 respondents were selected using a purposive sampling technique. Anthropometric measurements included Body Mass Index (BMI) and abdominal circumference. Metabolic parameters assessed were fasting blood sugar, blood pressure, and total cholesterol levels. Data were analyzed with descriptive and inferential statistics, including Pearson and Spearman correlation tests, and logistic regression analysis (p ≤ 0.05). Results: of 61.9% of respondents were classified as obese (BMI ≥ 25 kg/m²). Elevated fasting blood sugar was observed in 90.5% of respondents, with 42.9% classified as pre-diabetic and 47.6% diagnosed with diabetes. Hypertension was present in 19% of respondents, while 26.2% had high cholesterol levels. A significant correlation was found between obesity and both diabetes (p = 0.036) and hypertension (p = 0.005). Discussion: The findings demonstrated obesity as a major risk factor for diabetes and hypertension, with excessive body fat contributing to insulin resistance and neurohormonal dysregulation. The study underscores the need for early intervention through lifestyle modifications and workplace health programs. Conclusion: The high prevalence of obesity in this population is strongly linked to an increased risk of metabolic disorders. Targeted interventions focusing on dietary regulation, physical activity promotion, and regular health screenings are essential to mitigate these risks.Keywords: Obesity, diabetes, hypertension, metabolic risk.